Julia Margaret Cameron - a poetry of photography - Fazio, Nichole J. (Bodleian Library, 2023)
"A celebration of pioneering Victorian photographer Julia Margaret Cameron, and the artistic connection between her poetry and her photography. Renowned photographer Julia Margaret Cameron is famous for her evocative portraits of eminent Victorians, including John Herschel, Alfred Tennyson, Henry Taylor, George Frederic Watts, Ellen Terry and Julia Stephen. This study of her work reveals how deeply she was convinced of the poetic possibilities of her medium, particularly its capacity for suggestive rather than literal meaning. She did not get it right on all counts, and her practice violated the aesthetic orthodoxy of the day. But the blurring of the 'real' subject before her lens created unparalleled possibilities for a broader pursuit of the sublime and beautiful. Drawing on over 100 items from the photographic collections at the Bodleian Library and Ashmolean Museum at the University of Oxford, as well as comparative works of art, this book celebrates a collection that illustrates the aesthetic development of the photographer from her earliest pictures to her most poetic photographs. It also includes her own poetry and the key images she created for her extraordinary Illustrations to Tennyson's Idylls of the King, and Other Poems, demonstrating her fascination with the artistic connection between poetry and photography"--Publisher's description
Based on exhibition and symposium held at Bodleian Library, 20 January, 2016
Includes bibliographical references (pages 267-274) and index
Keywords: Cameron, Julia Margaret -- 1815-1879; Geschichte 1865-1875; Porträtfotografie; Cameron, Julia Margaret / 1815-1879; Cameron, Julia Margaret - 1815-1879; Photography, Artistic / Exhibitions; Portrait photography / Exhibitions; Photographie artistique - Expositions; Portraits (Photographie) - Expositions; Biographies